The Long Détente : Changing Concepts of Security and Cooperation in Europe, 1950s-1980s - Villaume, Poul; Bange, Oliver (Book collections on Project MUSE., 2017)
"This book sets out to discuss what has been termed as the 'second Cold War, ' that is, the deterioration of superpower-relations in the late 1970s and 1980s. Its goal is to present the European perspective on this period. As such, it is a collection of pieces of evidence, which--taken together--leads to an argument that goes against the grain of the established narrative. This is the argument that a 'long detente' existed between East and West, that it existed and lasted for good (economic, security-political, societal) reason, and that it had a profound impact on the eventual outcome of the conflict between East and West and the quintessentially peaceful framework in which this 'endgame' was played. The attractiveness of the book stems from its combination of profound research, resulting in an argument that runs against the grain of conventional wisdom"--Provided by publisher.